Are we doing enough? Evaluation of the Polio Eradication Initiative in a district of Pakistan's Punjab province: a LQAS study - Mushtaq, Muhammad Umair (BioMed Central, 2010)
BACKGROUND: The success of the Global Polio Eradication Initiative was remarkable, but four countries - Afghanistan, Pakistan, India and Nigeria - never interrupted polio transmission. Pakistan reportedly achieved all milestones except interrupting virus transmission. The aim of the study was to establish valid and reliable estimate for: routine oral polio vaccine (OPV) coverage, logistics management and the quality of monitoring systems in health facilities, NIDs OPV coverage, the quality of NIDs service delivery in static centers and mobile teams, and to ultimately provide scientific evidence for tailoring future interventions. METHODS: A cross-sectional study using lot quality assessment sampling was conducted in the District Nankana Sahib of Pakistan's Punjab province. Twenty primary health centers and their catchment areas were selected randomly as 'lots'. The study involved the evaluation of 1080 children aged 12-23 months for routine OPV coverage, 20 health centers for logistics management and quality of monitoring systems, 420 households for NIDs OPV coverage, 20 static centers and 20 mobile teams for quality of NIDs service delivery. Study instruments were designed according to WHO guidelines. RESULTS: Five out of twenty lots were rejected for unacceptably low routine immunization coverage. The validity of coverage was questionable to extent that all lots were rejected. Among the 54.1% who were able to present immunization cards, only 74.0% had valid immunization. Routine coverage was significantly associated with card availability and socioeconomic factors. The main reasons for routine immunization failure were absence of a vaccinator and unawareness of need for immunization. Health workers (96.9%) were a major source of information. All of the 20 lots were rejected for poor compliance in logistics management and quality of monitoring systems. Mean compliance score and compliance percentage for logistics management were 5.4 ± 2.0 (scale 0-9) and 59.4% while those for quality of monitoring systems were 3.3 ± 1.2 (scale 0-6) and 54.2%. The 15 out of 20 lots were rejected for unacceptably low NIDs coverage by finger-mark. All of the 20 lots were rejected for poor NIDs service delivery (mean compliance score = 11.7 ± 2.1 [scale 0-16]; compliance percentage = 72.8%). CONCLUSION: Low coverage, both routine and during NIDs, and poor quality of logistics management, monitoring systems and NIDs service delivery were highlighted as major constraints in polio eradication and these should be considered in prioritizing future strategies.